Gargle pool PCR testing in a hospital during medium and high SARS-CoV-2 incidence. (September 2022) - Kheiroddin, P.; Gaertner, V.D.; Schöberl, P.; Fischer, E.; Niggel, J.; Pagel, P.; Lampl, B.M.J.; Ambrosch, A.; Kabesch, M.
Summary: Background: Hospitals need to be protected from SARS-CoV-2 infections to protect vulnerable patients. Thus, a safe, efficient, and cost-effective SARS-CoV-2 testing system for hospitals, in addition to standard hygiene measures and vaccination of staff, is necessary. Here we report on the feasibility and performance of a pool real-time reverse-transcriptase polymerase-chain-reaction (rRT-PCR) test system at, medium and high incidence. Methods: We implemented a testing concept based on gargling at home and pooling of samples in the hospital before PCR testing in the laboratory. We used two PCR systems (point of care and standard 96-well plate system) to adapt to challenges in the hospital setting and respond to a rising incidence in the Omicron wave. Findings: During our 10-week study period, we performed 697 pool PCRs (8793 tests in total) and identified 65 asymptomatic staff members by pool PCR and 94 symptomatic staff members by positive individual PCR. Virus loads in those detected by pool testing were significantly lower ( P <0.001). The test system remained workable even during the peak of the Omicron wave and no outbreaks occurred in any specific area of the hospital during the study period. Unvaccinated individuals were over-represented in the positively tested (37% vs 22% positive tests, P =0.04). The test procedure was well accepted by a majority of the hospital staff (84%). Conclusion: Repeated gargle pool rRT-PCR testing can be implemented quickly in hospitals and is an effective, easily adaptable and well-accepted test system for hospitals, even during phases with very high infection rates.